The Use of Augmented Reality and Virtual Reality Technologies in Teaching Foreign Languages - Rudnik, Yuliia (Educological discourse, 2023)
The article is devoted to analyzing the educational potential of augmented reality (AR) and virtual reality (VR) technologies in teaching foreign languages, specifically in the professional training of future teachers. The possibility and benefits of introducing AR technologies in the system of teachers’ professional training are based on the experience of the discipline «Modern Technologies of Teaching a Foreign Language to Preschool Children», which is taught during the first (bachelor’s) level of education to students of the 012 Preschool Education Specialty at the Faculty of Pedagogical Education in Borys Grinchenko Kyiv University. The literature analysis and the description of the empirical experience of the interaction and implementation of AR and VR technologies in the course content are the major research methods used in this article. The article performs an analysis of the advantages and disadvantages of AR and VR technologies in foreign language teaching. The didactic potential of both aforementioned technologies is identified, including the improved learning environment, increased motivation, interaction, and content retention, the richness of multimedia modes, better visualization, and suitability for special learning needs. The article emphasizes the influence on multiple language skills and vocabulary development (vocabulary acquisition, phonics, pronunciation, comprehension, writing, reading, speaking, improved communication, and general learning skills). The data received proves the suitability and benefits of implementing current AR technologies in the professional training of future teachers and language teaching in general, as opposed to VR technologies that are limited due to their drawbacks that outweigh their current advantages, but still allow them to be considered a very powerful tool in the near future. Still, their partial accessibility by learners gives them the right to be used in terms of the realization of individual approaches. As a result of this article, a list of AR and VR technologies that could be used in foreign language teaching is revealed. The perspective of future research could focus on the analysis of specific technologies from AR or VR groups